-3+19x=11x+3+50

Simple and best practice solution for -3+19x=11x+3+50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+19x=11x+3+50 equation:



-3+19x=11x+3+50
We move all terms to the left:
-3+19x-(11x+3+50)=0
We add all the numbers together, and all the variables
19x-(11x+53)-3=0
We get rid of parentheses
19x-11x-53-3=0
We add all the numbers together, and all the variables
8x-56=0
We move all terms containing x to the left, all other terms to the right
8x=56
x=56/8
x=7

See similar equations:

| -2m+3=8 | | 5x+7=-2x-10 | | 5(y+6)=-3(4y-9)+2y | | 9p=10P+10 | | 28-4x=-8x-32 | | y/5+8=10 | | 6/390=4/y | | -30=10j | | -4(x+7)=44 | | 10-19.95=139.95x | | 46+12x=546-8 | | 3/2(n−6)=5n−43 | | 56+x+65+65=180 | | –30=10j | | 2-3(x-8)=2x-4 | | 4x-(2x+1)-7=2/3(3x-3) | | 4(m+4=48 | | 6x+5x-7x+3-x=48 | | x+58+81+49=180 | | 5x2−90=0 | | (x+7)=–3(2x+14) | | 5x=7=-2x-10 | | 61+x+60=70 | | 2x-5(x-5)=-4+3x-13 | | 2x+(2x/3)=35 | | 3x+6-7x+1=x | | -15x+4(3x-7)=4/9x-3/2 | | 9/n=-4 | | 2x+(2x/3)=45 | | 2X+3=5x+126 | | 2x+(2x/3)=4 | | .04/22=1/x |

Equations solver categories